LENGTH-WEIGHT RELATIONSHIP AND CONDITION FACTOR OF FOURFINGER THREADFIN (Eleutheronema tetradactylum Shaw, 1804) IN SEDATI, SIDOARJO - Rahman, Muhammad Arif; Wiadnya, Dewa Gede Raka; Harlyan, Ledhyane Ika; Setyohadi, Daduk; Mahsuna, Inna Rohmatul (Directorate of Research and Community Service (DRPM), 2024)
The fourfinger threadfin, Eleutheronema tetradactylum is one of economic demersal species in Indonesia. Information of its biology was needed to ensure the sustainable fisheries management of this species. This study aimsto estimate the lengthweight relationship and condition factor of E. tetradactylum landed in Sedati, Sidoarjo, East Java. In total, 649 samples were randomly collected from Sedati Fishing Base during the study. The results indicated that E. tetradactylum has negative allometric growth pattern (b = 2.8, p<0.05), means the growth of length was faster than weight. In addition, the average value of relative weight condition factor (kn) was 1.01, which is greater than or equal to 1, means E. tetradactylum live in good growth conditions. This finding contributes to managing E. tetradactylum fishery in the north Java waters, especially in East Java. As this study was conducted from unsexed samples, future research with focuse on sexed samples is suggested to give more comprehensive result.